BAURAN PEMASARAN 7P DAN PENGARUHNYA TERHADAP KEPUASAAN PELANGGAN RUMAH MAKAN MR. TETO PUSAT, PERINTIS KEMERDEKAAN, KOTA YOGYAKARTA - Maimunah Maimunah; Uju Suji’ah (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
This study aims to determine the effect of marketing mix (product/X1, price/X2, place/X3, promotion/X4, people/X5, process/X6, physical evidence/X7) on customer satisfaction, as measured by the partial significance test (Test t) and simultaneous significance test (F test), the data analysis technique used to answer the hypothesis with multiple linear regression test. The population in this study were consumers who had bought Mr. Teto Pusat, Pioneer of Independence, Yogyakarta City. The sampling technique used purposive sampling method, with a total sample of 100 people.The results of this study indicate that: 1). The product has an effect on customer satisfaction, this is evidenced by the significance of 0.453 <0.05, the value of tcount (5.518) > ttable (1.658); price has no effect on customer satisfaction, this is evidenced by the significance of 0.099 <0.05, the value of tcount (0.867) > ttable (1.658); place has no effect on customer satisfaction, this is evidenced by the significance of 0.015 <0.05, the value of tcount (0.106) > ttable (1.658); promotion has an effect on customer satisfaction, this is evidenced by the significance of 0.202 <0.05, the value of tcount (2,079) > ttable (1,658); people have no effect on customer satisfaction, this is evidenced by the significance of -0.152 <0.05, the value of tcount (-1.131)> ttable (1.658); the process has an effect on customer satisfaction, this is evidenced by the significance of 0.637 <0.05, the value of tcount (5.240) > ttable (1.658); physical evidence has an effect on customer satisfaction, this is evidenced by the significance of 0.315 <0.05, the value of tcount (2,311)> ttable (1,658). 2). Marketing mix (product/X1, price/X2, place/X3, promotion/X4, people/X5, process/X6, physical evidence/X7) has an influence on customer satisfaction, this is evidenced by a significance of 0.000 < 0.05, the value Fcount (16.080) > Ftable (2.10). 3). Multiple linear regression equation obtained Y = 0.431 + 0.453X1 + 0.099X2 + 0.015X3 + 0.202X4 – 0.152X5 + 0.637X6 + 0.315X7. 4). The result of the coefficient of determination (R2) is 0.516, indicating that the marketing mix (product/X1, price/X2, place/X3, promotion/X4, people/X5, process/X6, physical evidence/X7) has an effect on customer satisfaction of 51, 6%, while the remaining 48.4% was influenced by other factors not examined